THE EFFECT OF WORKLOAD AND FINANCIAL COMPENSATION ON WORK MORALE WITH WORK ENGAGEMENT AS A MODERATING VARIABLE - Dahlan, Mardiana; Syahir Natsir; Adfiyani Fadjar (Master of Management Study Program, Faculty of Economics and Business, Tadulako University, 2024)
This study aims to analyse the effect of workload and financial compensation on work enthusiasm with work engagement as a moderating variable in the expenditure treasurer of the Regional Work Unit (SKPD) of Tojo Una Una Regency. This research is a type of quantitative research, with the census method, namely using forty-one Tojo Una Una Regency SKPD expenditure treasurers as the population. The analytical tool used is SEM-PLS, data collection through google form media. The results of this study indicate that (1) workload has a negative and significant effect on the morale of SKPD expenditure treasurers of Tojo Una Una Regency (2) financial compensation has a positive and significant effect on the morale of SKPD expenditure treasurers of Tojo Una Una Regency (3) work engagement has a negative and significant effect as a moderator of the relationship between workload and morale of SKPD expenditure treasurers of Tojo Una Una Regency (4) work engagement has a positive and significant effect as a moderator of the relationship between financial compensation and morale of SKPD expenditure treasurers of Tojo Una Una Regency (4) work engagement has a positive and significant effect as a moderator of the relationship between financial compensation and morale.